The Influence of Accountability, Transparency, and Moral Reasoning on the Audit Quality of the Inspectorate of West Sulawesi Province - Hanif AR, Muh Amir; Nirwana, Nirwana; Darmawati, Darmawati (Paradoks : Jurnal Ilmu Ekonomi, 2025)
High-quality audits are essential for fostering transparency and accountability in public financial management, ultimately enhancing public trust. This study examines the effects of accountability, transparency, and moral reasoning on audit quality at the Inspectorate of West Sulawesi Province. Data were collected from 50 auditors with an 80% response rate using a quantitative approach and survey method. The results reveal that accountability and transparency significantly influence audit quality, while moral reasoning shows no significant effect. These findings align with agency theory, highlighting the role of transparency and accountability in reducing information asymmetry. The study emphasizes the need for policies that strengthen accountability and transparency in public sector audits. The results provide practical implications for improving audit quality and serve as a foundation for future research with broader scope and additional variables.